2018
DOI: 10.1016/j.ndteint.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Image processing based quantitative damage evaluation in composites with long pulse thermography

Abstract: Pulsed thermography is a contactless and rapid non-destructive evaluation (NDE) technique that is widely used for the inspection of fibre reinforced plastic composites. However, pulsed thermography uses expensive and specialist equipment such high-energy flash lamps to generate heat into the sample, so that alternative thermal stimulation sources are needed. Long pulse thermography was recently developed as a cost-effective solution to enhance the defect detectability in composites by generating step-pulse hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Active IR-thermographic methods such as cooling down thermography (CDT) [5] or long pulsed thermography (LPT) [6,7] give satisfactory results for similar defects in composites. In this paper, PT thermography in the range of long pulses is explored, even that heat accumulation phenomenon may occur for subsurface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Active IR-thermographic methods such as cooling down thermography (CDT) [5] or long pulsed thermography (LPT) [6,7] give satisfactory results for similar defects in composites. In this paper, PT thermography in the range of long pulses is explored, even that heat accumulation phenomenon may occur for subsurface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Although a moderately shallow defect can be detected using IRT after exposure to intensive heat over a short period of time, previous studies have shown that flash thermography for IR inspection is effective for defect detection in thin structural members (e.g. wind turbines) . As the present study mainly focuses on delamination detection in concrete members of bridges, which are generally over 200‐mm‐thick, a relatively long period of time exposure to direct solar radiation could make the IR inspection more effective.…”
Section: Resultsmentioning
confidence: 89%
“…wind turbines). 24,[35][36][37][38] As the present study mainly focuses on delamination detection in concrete members of bridges, which are generally over 200-mm-thick, a relatively long period of time exposure to direct solar radiation could make the IR inspection more effective. Figure 10c shows the total heat input required to generate absolute thermal contrast of 1 C for different delamination sizes under two different heating rate and heating durations (z = 50 mm).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Recently, the thermographic approach for the material integrity and damage analysis becomes promising as the nondestructive testing technique (Ciampa et al, 2018;Wang et al, 2018Wang et al, , 2019. The current state of practice in thermal integrity analysis of civil engineering materials is to measure temperature using thermocouples or infrared probes, then estimate the temperature distributions within the structures.…”
Section: Introductionmentioning
confidence: 99%